Synthesis and Evaluation of Quinazoline Derivative as Antimicrobial and Surface Active Agent - Saini, Sangita; Kaur, Harmeet; Garg, Arun; Singh, S.K.; Mishra, D.N. (Asian Journal of Chemistry, 2011)
Anthranilic acid reacted with benzoyl chloride to produce 2-substituted 3,1-benzoxazin-4-one which was used as starting material to synthesize 3-[bis(4-fluorophenyl)methylidene]amino-2-phenylquinazolin-4(3H)-one. The products were subjected to reaction with required mole of sodium lauryl sulfate to produce a novel surfactant having antibacterial and surface active properties which can be used in the manufacturing of drugs, cosmetics, pesticides or can be used as antibacterial additives. The surface active properties as surface and interfacial tension, cloud point, foaming height, wetting time and emulsification power were determined. The antimicrobial activities were also screened.